Colonoscopic Findings in Patients with Bleeding Per-rectum in Colonoscopy Center at Rizgary Teaching Hospital, Erbil, Iraq - Mahmood Khudhur; Ali Al Dabbagh (Al-Anbar Medical Journal, 2023)
Background: Rectal bleeding is commonly seen in daily practice. The colonoscopy is an essential diagnostic tool in detecting the various causes of this clinical entity.Objectives: We aimed to detect the different pathological lesions in patients with rectal bleeding using colonoscopy and to find the correlation between colonoscopic findings and the age and gender of the patients.                             Materials and Methods: This prospective cross-sectional study was conducted at the center of endoscopy and colonoscopy at Rizgary Teaching Hospital throughout the period from April 2018 to April 2019.  Patients with bleeding from the rectum and subjected to colonoscopy of any age and gender were enrolled in the current study. Data regarding the age, gender, duration, family history of colorectal cancer, whether the bleeding was fresh or mixed with stool, spontaneous stoppage of bleeding or not, and the colonoscopic findings were recorded for every participant.Results: Of 91 patients with rectal bleeding, there were 55 (60.4%) male. The most affected age group was over 40 years old (n = 47, 51.6%). Only 11 (12.1%) of the participants gave a family history of colorectal cancer. Around three-quarters of the cases involved chronic bleeding. The bleeding was fresh in 60 (65.9%) cases. The majority of the bleeding (n = 74, 81.3%) stopped spontaneously. Hemorrhoids (49.45%) were the most common colonoscopic finding in patients with rectal bleeding, followed by no abnormality (18.68%), and the least diverticular disease (2.2%). There was a statistically significant difference between the age of the patient and the cause of rectal bleeding (P-value = 0.042). However, there was no such correlation regarding the patient's gender (P-value = 0.196). Conclusion: Hemorrhoids were the most common colonoscopic finding in patients with rectal bleeding. The age of the patient can determine the cause of the rectal bleeding.